Epidemiology of cerebral palsy in low‐ and middle‐income countries: preliminary findings from an international multi‐centre cerebral palsy register. (24th May 2021) - Jahan, Israt; Muhit, Mohammad; Hardianto, Denny; Laryea, Francis; Chhetri, Amir Banjara; Smithers‐Sheedy, Hayley; McIntyre, Sarah; Badawi, Nadia; Khandaker, Gulam
Abstract : Aim: To describe the epidemiology of cerebral palsy (CP) in children from low‐ and middle‐income countries (LMICs) using data from the Global Low‐ and Middle‐Income Country CP register (GLM‐CPR). Method: The GLM‐CPR is a multi‐country initiative that combines and compares data from children with CP (<18y) in LMICs. Children with CP are registered after detailed neurodevelopmental assessment by a multidisciplinary medical team using a harmonized protocol. Data are collected on agreed core variables. Descriptive analyses are completed to report findings from participating countries. Results: Between January 2015 and May 2019, 2664 children were recruited from Bangladesh, Nepal, Indonesia, and Ghana (mean age [SD] at assessment: 7y 8mo [4y 8mo], 95% confidence interval 7y 6mo−7y 11mo; male [ n =1615] 60.6%, female [ n =1049] 39.4%). Overall, 86.6% children acquired CP prenatally and perinatally (e.g. preterm birth, birth asphyxia, neonatal encephalopathy). Median age at CP diagnosis was 3 years. Moreover, 79.2% children had spastic CP and 73.3% were classified in Gross Motor Function Classification System levels III to V. Notably, 47.3% of children never received rehabilitation services (median age at receiving rehabilitation services was 3y; 12.7% received assistive devices) and 75.6% of school‐age children had no access to education. Interpretation: Population‐based data show that the proportion of severe cases of CP is very high in LMICs. Children with CP in LMICs lack access to rehabilitation and educational services and a large proportion of children have potentially preventable risk factors, for example, birth asphyxia and neonatal infections. Delayed diagnosis, severe motor impairments, and lack of rehabilitation in most children call for urgent action to identify preventive opportunities and promote early diagnosis and intervention for children with CP in LMICs. What this paper adds The proportion of severe cases of cerebral palsy (CP) is very high in rural low‐ and middle‐income countries (LMICs). Children with CP in LMICs lack access to rehabilitation and educational services. A large proportion of children with CP in LMICs have potentially preventable risk factors. What this paper adds: The proportion of severe cases of cerebral palsy (CP) is very high in rural low‐ and middle‐income countries (LMICs). Children with CP in LMICs lack access to rehabilitation and educational services. A large proportion of children with CP in LMICs have potentially preventable risk factors. This original article is commented by Paneth on page 1245 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Epidemiología de la parálisis cerebral en países de ingresos bajos y medianos: hallazgos preliminares de un registro internacional multicéntrico de parálisis cerebral: Objetivo: Describir la epidemiología de la parálisis cerebral (PC) en niños de países de ingresos bajos y medios (PIBM) utilizando datos del registro mundial de PC de países de ingresos bajos y medios (GLM‐CPR). Método: El GLM‐CPR es una iniciativa de varios países que combina y compara datos de niños con parálisis cerebral (<18 años) en PIBM. Los niños con parálisis cerebral se registran después de una evaluación detallada del desarrollo neurológico realizada por un equipo médico multidisciplinario utilizando un protocolo armonizado. Los datos se recopilan sobre las variables fundamentales acordadas. Se completan análisis descriptivos para informar los hallazgos de los países participantes. Resultados: Entre enero de 2015 y mayo de 2019, se reclutaron 2664 niños de Bangladesh, Nepal, Indonesia y Ghana (edad media [DE] en la evaluación: 7 años 8 meses [4 años 8 meses], intervalo de confianza del 95% 7 años 6 meses−7 años 11 meses; varón [ n = 1615] 60, 6%, mujeres [ n = 1049] 39, 4%). En general, el 86, 6% de los niños adquirieron parálisis cerebral prenatal y perinatalmente (por ejemplo, parto prematuro, asfixia al nacer, encefalopatía neonatal). La mediana de edad en el momento del diagnóstico de PC fue de 3 años. Además, el 79, 2% de los niños tenían parálisis cerebral espástica y el 73, 3% se clasificaron en los niveles III a V del sistema de clasificación de la función motora gruesa. y el 75, 1% de los niños en edad escolar no tenían acceso a la educación. Interpretación: Los datos basados en la población muestran que la proporción de casos graves de PC es sustancialmente alta en los países de ingresos bajos y medianos. Los niños con parálisis cerebral en los países de ingresos bajos y medianos carecen de acceso a servicios de rehabilitación y educación y una gran proporción de niños tienen factores de riesgo potencialmente prevenibles, por ejemplo, asfixia al nacer e infecciones neonatales. El diagnóstico tardío, las deficiencias motoras graves y la falta de rehabilitación en la mayoría de los niños exigen una acción urgente para identificar oportunidades preventivas y promover el diagnóstico y la intervención tempranos para los niños con parálisis cerebral en los países de ingresos bajos y medianos. Epidemiologia da paralisia cerebral em países de baixa e média renda: achados preliminares de um registro de paralisia cerebral multicêntrico internacional: Objetivo: Descrever a epidemiologia da paralisia cerebral (PC) em crianças de baixa e media renda (PBMR) usando dados do Registro Global de PC de países de baixa e média renda (GBM‐ RPC). Método: O GBM‐RPC é uma iniciativa de vários países que combina e compara dados de crianças com PC (<18a) em PBMRs. Crianças com PC são registradas após detalhada avaliação neurodesenvolvimental por uma equipe médica multidisciplinar e usando um protocol harmonizado. Os dados são coletados sobre variáveis centrais com as quais o grupo concordou. Análises descritivas são realizadas para reportar os achados dos países participantes. Resultados: Entre Janeiro de 2015 e Maio de 2019, 2.664 crianças foram recrutadas de Bangladesh, Nepal, Indonesia, e Gana (média de idade [DP] na avaliação: 7a 8m [4a 8m], intervalo de confiança a 95% 7a 6m−7a 11m; sexo masculino [ n =1.615] 60, 6%, feminino [ n = 1.049] 39, 4%). Ao todo, 86, 6% das crianças adquiriram PC pré‐natal e perinatalmente (ex: nascimento prematuro, asfixia no nascimento, encefalopatia neonatal encephalopathy). A idade mediana do diagnóstico de PC foi 3 anos. Além disso, 79, 2% ds crianças tinham PC espástica e 73, 3% foram classificadas nos níveis do Sistema de Classificação da Função Motora Grossa III a V. Notavelmente, 47, 3% das crianças nunca receberam serviços de reabilitação (idade mediana de receber os serviços de reabilitação foi 3a; 12, 7% receberam dispositivos assistivos) e 75, 1% das crianças em idade escolar não tinham nenhum acesso a educação. Interpretação: Dados populacionais mostram que a proporção de casos severos de PC é substancialmente alta em PBMRs. As crianças com PC nos PBMRs carecem de acesso a serviços de reabilitação e educação e uma grande proporção tem fatores de risco potencialmente preveníveis, como asfixia no nascimento e infecções neonatais. O atraso no diagnóstico, a severidade do comprometimento motor, e a falta de reabilitação para a maior parte das crianças clamam por ações urgentes para identificar oportunidades de prevenção e promover diagnóstico e intervenção precoce para crianças com PC em PBMRs.